(untitled) (Journal of the College of Basic Education, 2026)
The Holy Quran has greatly influenced poets, and this influence has been evident since its revelation until the present day. However, the process of quoting from the Quranic text has varied according to the poet’s culture and the environment in which they live. The Quranic story is one of the most captivating poetic themes, and poets have sought to utilize it in various poetic forms. Our research examines the story of the Virgin Mary, peace be upon her, and its influence on contemporary Najaf poetry. Poets have benefited from the story through allusive intertextuality by incorporating the Quranic meanings it contains into their poems. The poets had a goal, including embodying the content of patience, willpower, and endurance of pain in the character of the Virgin Mary. In addition, the poets have benefited from the artistic aspects of the story, which is reflected in their poems by producing artistic images characterized by novelty and innovation.